VACCINATION CONSENT OF THE MOST VULNERABLE PEOPLE IN TIMES OF PANDEMIC CRISIS - VÉRON, Paul (MEDECINE LEGALE DROIT MEDICAL, 2025)
Vulnerable people were the first to be affected by the vaccination campaign against Covid-19, in particular the elderly living in nursing homes. For these people, the justification of vaccination, with regard to a risk benefit ratio, does not raise the same questions as for other parts of the population, in particular minors. Nevertheless, the question of respect for their will has arisen, in particular for people with impaired jugement.